Istikhdām kitāb “Mumtāz” ka-kitāb ta‘līmī li-ta‘līm ‘ilm an-naḥw fī al-madrasah al-mutawassiṭah Insān Cendikia Mandirī fī Sīdoārjo - Al Fahrezy, Moh. Abdurrahman; Lailatul Qomariyah; Muhammad Dzikru Alfin Maulaya (Program Studi Pendidikan Bahasa Arab, 2025)
In this era, many schools in Indonesia recognize the importance of Arabic language, particularly Nahwu science.